Phenotypes of intimate partner violence among women experiencing infertility in Kano, Northwest Nigeria. Issue 1 (April 2016) - Iliyasu, Zubairu; Galadanci, Hadiza S.; Abubakar, Sanusi; Auwal, Maryam S.; Odoh, Chisom; Salihu, Hamisu M.; Aliyu, Muktar H.
Abstract: Objective: To determine the prevalence of and risk factors for intimate partner violence (IPV) among women attending a large urban fertility clinic in Kano, Nigeria. Methods: Interviewers administered questionnaires to a cross-section of women attending an infertility clinic in Northwest Nigeria, regarding their experience of IPV and associated factors. Results: In total, 373 individuals were interviewed. Of the individuals interviewed, 134 (35.9%; 95% confidence Interval [CI] 31.1%–41.0%) had experienced at least one form of IPV in the preceding year. Of the 134 patients who had encountered violence, 126 (94.0%), 111 (82.8%), 47 (35.1%), and 25 (18.7%) had experienced psychological, sexual, verbal, and physical forms of violence, respectively. Of the affected individuals, 34 (25.4%) experienced multiple forms of violence, with spouses being the main perpetrators. A lack of formal education (adjusted odds ratio [OR] 2.21; 95%CI 1.21–7.43), employment in the informal sector (OR 2.01; 95%C: 1.02–4.52), and having an unemployed spouse (OR 1.56; 95%CI 1.02–3.15) or one with low level of education (OR 2.32; 95%CI 1.87–4.21) were independently associated with IPV. Conclusion: In this setting, women who were infertile experienced a high incidence of IPV. Women presenting at fertility clinics should be screened for IPV and provided with links to appropriate support services.